Improving Coherence of The Students’ Sentences by Applying Thematic Progression And Personal Blog In The Sentence-Based Writing Class - Arif Suryo Priyatmojo (UIN Salatiga, 2012)
This study was aimed at describing what kinds of thematic progression patterns mostly employed by the students, describing how to apply thematic progression theory and personal blog in the sentence-based writing class, and finding out whether the use of thematic progression theory and personal blog give positive significances to coherence of the students’ sentences. This is an action research study employing two cycles. The subject of the study was 24 students of group 2, in a class of sentence-based writing (SBW), and the object of the study was students’ sentences created by the students in the teaching and learning process (TLP). The result of the study shows that thematic progression patterns moslty employed by the students are constant theme pattern followed by zig zag and multiple theme patterns. In TLP, the materials were devided and given to the students in two cycles. The first cycle focused on introducing the thematic progression theory and its kinds of patterns. Then, in the next cycle the students focused on sharing ideas with other classmates via individual blogs. Based on the result of the study, teaching SBW using thematic progression theory gives its positive significance by varied patterns used by the students. It can be seen from the analysis of the students’ sentences from pretest, paragraf 1, paragraf 2, paragraf 3 and posttest. The students also give positive responses upon its teaching and learning process using thematic progression and personal blogs based on the pre and post test questionnaire data. It is hoped that the result of the study gives positive contribution to the students in preparing them to write in bigger contexts - paragraph-based writing, genre-based writng and academic writing in the next coming semesters. Keywords: Thematic Progression; Theme-Rheme; Thematization; Personal Blog